Allosteric regulation of the biotin-dependent enzyme pyruvate carboxylase by acetyl-CoA - Abdussalam Adina-Zada (2018)
The activity of the biotin-dependent enzyme pyruvate carboxylase from many organisms is highly regulated by the allosteric activator acetyl-CoA. A number of X-ray crystallographic structures of the native pyruvate carboxylase tetramer are now available for the enzyme from Rhizobium etli and Staphylococcus aureus. Although all of these structures show that intersubunit catalysis occurs, in the case of the R. etli enzyme, only two of the four subunits have the allosteric activator bound to them and are optimally configured for catalysis of the overall reaction. However, it is apparent that acetyl-CoA binding does not induce the observed asymmetrical tetramer conformation and it is likely that, under normal reaction conditions, all of the subunits have acetyl-CoA bound to them. Thus the activation of the enzyme by acetyl-CoA involves more subtle structural effects, one of which may be to facilitate the correct positioning of Arg 353 and biotin in the biotin carboxylase domain active site, thereby promoting biotin carboxylation and, at the same time, preventing abortive decarboxylation of carboxybiotin. It is also apparent from the crystal structures that there are allosteric interactions induced by acetyl-CoA binding in the pair of subunits not optimally configured for catalysis of the overall reaction. ©The Authors Journal compilation ©2012 Biochemical Society.